Effects of Fitball Exercise on Body Composition, Flexibility, Muscular Strength-Endurance and Aerobic Capacity in Obese Working-Age Women - Arunya Buttichak; Sarocha Namboonlue; Nattha Muangritdech; Palakorn Sriwiset; Chaiyawat Namboonlue (OVS LLC, 2023)
The study purpose was to examine and compare the effects of fitball exercise on body composition, flexibility, muscular strength-endurance and maximum oxygen consumption (VO2max) in obese working-age women.   Materials and methods. Twenty-six working-age women with obesity (BMI ≥ 25.0 kg/m2) aged between 40 and 50 years were divided into 2 groups: 1) fitball exercise group (FEG) and 2) control group (CG). The training lasted 12 weeks with sessions of 60 min/day and 3 days per week. All parameters were measured at 1 day prior to (PRE; pre-training), 1 day after 6 weeks (MID; middle-training) and within 1 day after 12 weeks (POST; post-training) of the training period. Results. After the 6-week training, the FEG showed substantial improvement in body weight, BMI, back extension, leg strength, 60 second chair stand (60SCST) and VO2 max (-0.92%, -1.34%, 12.74%, 27.19%, 25.79% and 10.75%, respectively, p < 0.05) when compared to the CG. Similarly, after the 12-week training, the FEG showed a significantly larger improvement in body weight, BMI, fat mass, sit and reach, back extension, leg strength, 60SCST and VO2max(-1.14%, -2.19%, -1.92%, 54.31%, 27.31%, 33.50%, 37.02% and 24.05%, respectively, p < 0.05) compared to the CG. Conclusions. Fitball exercise training is effective in improving body composition, flexibility and muscular strength-endurance as well as increasing the aerobic capacity in female workers with obesity.